(3TQM Yjhf GdMceI dGHf SjfGs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3jhSa Hf EHQGgje Hf CHj GdcQe s)
(3ChdgG (B:s
(3GeG HYO aEf cJGH Yjhf GdMceI dLhGeY cdeGJ GdMceGA aSCdfi HYV GdCYRI ef GdCUMGH s
(3BNQgG (B:s
(3Gdgi SQi dc ecTha hGfG Edjc edgha s
(3hgPG GdcJGH jMJhi Ydi KdGKI CbSGe GdChd efWb hGdKGfi GdWHjYI hGdKGdK GdGdgjGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs